Scales and Universality in Few-Body Systems - Frederico, T.; Tomio, Lauro [UNESP]; Delfino, A.; Hadizadeh, M. R. [UNESP]; Yamashita, Marcelo Takeshi [UNESP] (Springer Wien, 2011)
The role of scales in the physics of large few-body systems is reviewed. They are evidenced by considering weakly-bound three and four particles, where point-like interactions are regularized and renormalized in a procedure characterized by the emergence of physical scales fixed by observables. The results obtained with renormalized zero-ranged two-body interactions are presented in the form of universal scaling plots, or correlations between observables, where we also consider results of several other model calculations, as well as experimental results obtained in nuclear physics and cold-atom laboratories. The universal correlations between few-body observables are useful to predict one in terms of another observable and we discuss applications in setting low energies properties of halo nuclei, molecular and cold atom systems.